Essential Oils of Alpinia monopleura and Their Antibacterial and Antioxidant Activity - Agung Wibawa Mahatva Yodha; Esti Badia; Musdalipah Musdalipah; Muhammad Azdar Setiawan; Nur Saadah Daud; Angriani Fusvita; Adryan Fristiohady; Sahidin Sahidin (Universitas Jenderal Soedirman, 2023)
Alpinia monopleura is an endemic plant which widespread and abundant in Sulawesi. Nevertheless, previous studies have not studied the chemical compound and biological activity. This study describes the chemical compounds and antibacterial and antioxidant properties of the essential oils isolated from A. monopleura. The essential oil was obtained by the hydro distillation method and interpreted by GCMS. Antibacterial properties were determined by the agar diffusion method, while DPPH and ABTS determined antioxidant activity. The most important components are α-caryophyllene, β-pinene, limonene, α-pinene, β-caryophyllene and caryophyllene oxide. Essential oils of leaves and fruit showed excellent antibacterial properties with a MIC strength of 31.3 μg/mL against Staphylococcus aureus ATCC 25023 and Escherichia coli ATCC 35218. The highest antioxidant effect was also shown by inhibiting ABTS and DPPH radicals, with IC50 strength ​​of essential oil obtained from the leaf being 15.60 and 19.42 μg/mL, respectively, while from the fruit were 10.44 and 11.93 μg/mL. These antibacterial and antioxidant properties indicate that essential oils have advantages in their use in the food and pharmaceutical industries.